Ca / Mg-based modified charcoal material as well as preparation method and application thereof

By acid-leaching activation and Ca/Mg modification treatment on the grapefruit peel, Ca/Mg-based modified biochar material was prepared, which solved the stability and cost problems of existing adsorbent materials when treating phosphorus-containing wastewater, achieved the effect of efficient adsorption of phosphate, and had the potential as a phosphorus fertilizer.

CN119524798AInactive Publication Date: 2025-02-28WUHUAN ENG +1

Patent Information

Application Number
CN202411527437.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When treating phosphorus-containing wastewater, existing adsorbent materials have problems such as large amount of material, difficulty in desorption after adsorption, and high treatment costs. The particle size of biochar is small and difficult to separate, and the material properties are greatly affected by raw materials and pyrolysis conditions.

Method used

The Ca/Mg-based modified bimetal modified biochar material was used to crush, sieve, wash and acid-lime activation of the grapefruit peel through pretreatment steps, and then thoroughly mix with CaO and MgO, impregnation modification and pyrolytic carbonization to prepare Ca/Mg-based modified biochar material with good stability.

Benefits of technology

This material has good stability, good pH adaptability, good adsorption effect, and can effectively adsorb phosphate. It is suitable for the treatment of complex water environments and has a smaller amount. The adsorbed material also has the potential as a phosphorus fertilizer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119524798A_ABST
    Figure CN119524798A_ABST
Patent Text Reader

Abstract

The invention discloses a Ca / Mg-based modified biochar material and a preparation method and application thereof, and the preparation method comprises the following steps: pretreatment: drying a biomass material shaddock peel, crushing, sieving, washing and drying, then carrying out acid leaching activation, washing again and drying to obtain high-activity biomass powder for later use; dipping modification: fully mixing the high-activity biomass powder obtained in the pretreatment step with CaO and MgO, adding distilled water, dipping under heating and stirring conditions, then carrying out solid-liquid separation, washing a filter cake for multiple times, freeze-drying, and sieving to obtain an intermediate product; the intermediate product is calcined, naturally cooled, washed and dried, and the Ca / Mg-based modified bimetallic modified charcoal material is obtained and can be applied to adsorption of phosphate in a wastewater solution as an adsorbent. The preparation method is simple, the raw materials are easy to obtain, the cost is low, the material stability is good, the pH adaptability is good, the adsorption effect is good, and the method is suitable for water environments with more complex pollution factors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a biochar material and a preparation method and application thereof, in particular to a Ca / Mg-based modified biochar material and a preparation method and application thereof. Background Art

[0002] Phosphorus is used in large quantities as an industrial raw material and agricultural fertilizer. Large-scale industrial production and direct discharge of phosphorus-containing wastewater have led to serious eutrophication pollution of water bodies, making it a typical water pollution problem. In recent years, adsorption phosphorus removal technology has developed rapidly. The adsorption method is to use natural or artificial porous materials to enrich pollutants on the surface of the adsorbent through the interaction of the surface van der Waals force and electrostatic attraction on the pollutants, thereby separating them from the liquid phase system. The adsorption method can recover phosphorus in wastewater by treating phosphorus-containing wastewater, and make it into economical byproducts such as organic fertilizers, thereby realizing the recycling of phosphorus. In addition, adsorption phosphorus removal is also suitable for treating low-concentration phosphorus-containing wastewater, so it can be considered that adsorption phosphorus removal has a broad development prospect.

[0003] Adsorption materials commonly used in phosphorus-containing wastewater treatment mainly include silicon-based mesoporous materials, mesoporous sulfate materials, mesoporous metal oxide materials and carbon-based materials. Although the above materials have strong adsorption properties and high pollutant removal efficiency, they have the disadvantages of large material usage, difficult desorption of materials after adsorption, and high treatment costs. Therefore, it is necessary to find a material with low treatment cost, easy regeneration and good treatment performance.

[0004] Biochar is a black solid formed by pyrolysis of agricultural and forestry waste under anaerobic or completely anoxic conditions at high temperatures (300-700) °C. It has the characteristics of large specific surface area, developed pore structure, rich adsorption sites, strong chelating ability, and few functional groups. It is an excellent biological adsorption material that can not only reduce environmental pollution, but also turn waste into treasure, which is in line with the concept of energy conservation and environmental protection. However, biochar as an adsorbent also has characteristic limitations. Due to its small particle size, it is difficult to separate from the aqueous phase, which limits its application in the field of wastewater treatment; different raw materials, pyrolysis methods and conditions will also affect the performance of biochar, such as the difference in the adsorption effect of nutrient ions. By improving the surface properties and structure, modified biochar can obtain higher pollutant removal potential, which has become a hot topic in current research.

[0005] Publication No. CN 112191229 A discloses a preparation method and application of Mg / Ca loaded modified tobacco stalk biochar, wherein a Mg / Ca loaded tobacco stalk metal biochar composite material is prepared by MgCl2 pretreatment and eggshell doping, and tobacco stalks are used as biochar raw materials, which are derived from the residues of a single crop and have limited resources. In addition, although eggshells can be introduced as a calcium source, since eggshells also contain a certain proportion of organic matter and impurities, their introduction may also lead to the release of pollutants, which has a negative impact on the environment and is difficult to handle. In addition, excessive doping of eggshells may affect the overall structure and function of biochar, reducing its effectiveness in soil improvement and nutrient adsorption. CN 113522241 A "A kind of iron-magnesium modified biochar and its preparation method and use" selects iron-magnesium to modify biochar, synthesizes iron-magnesium modified biochar by impregnation-pyrolysis method, makes iron-magnesium oxide evenly distributed on the surface of biochar, utilizes iron-magnesium composite modified biochar to react with phosphorus in solution to generate complex precipitate crystals to remove phosphorus in water body, iron ions are easily hydrolyzed in water body, resulting in unstable material; Publication No. 117323963A "A kind of magnesium modified straw biochar and its preparation method and use" soaks straw in magnesium salt solution (the concentration of magnesium salt solution is 0.05-0.5 mol / L) and then carbonizes to obtain the magnesium modified straw biochar, which also has the problems of unstable material, poor absorption effect and poor pH adaptability of wastewater. Summary of the invention

[0006] The purpose of the present invention is to solve the above technical problems and provide a Ca / Mg-based modified biochar material with good material stability, good pH adaptability, good adsorption effect, and the ability to enhance the adsorption capacity of carbon materials for phosphate, which is suitable for water environments with more complex pollution factors.

[0007] The present invention also provides a method for preparing the above-mentioned Ca / Mg-based modified biochar material with a simple method and low cost.

[0008] The present invention also provides an application of the above-mentioned Ca / Mg-based modified biochar material.

[0009] The preparation method of the Ca / Mg-based modified bimetallic modified biochar material of the present invention comprises the following steps:

[0010] Pretreatment: After the biomass material is dried, it is crushed, sieved, washed and dried, and then acid-leached for activation, and then washed and dried again to obtain a highly active biomass powder, wherein the biomass material is grapefruit peel;

[0011] Impregnation modification: the highly active biomass powder obtained in the pretreatment step is fully mixed with CaO and MgO, distilled water is added, and the mixture is impregnated under heating and stirring conditions, and then solid-liquid separation is performed. After the filter cake is washed multiple times, it is freeze-dried and sieved to obtain a preliminary modified intermediate product;

[0012] Pyrolysis carbonization: The intermediate product obtained in the impregnation modification step is calcined under a protective atmosphere, and the product is naturally cooled, washed, and dried to obtain a Ca / Mg-based modified bimetallic modified biochar material.

[0013] In the pretreatment step, the biomass powder is sieved with a mesh size of 60-90 meshes.

[0014] In the pretreatment step, the acid used for acid leaching activation is hydrochloric acid, nitric acid or sulfuric acid with a concentration of 0.1 mol / L-1 mol / L, the solid-liquid mass ratio of the immersion is controlled to be (1:10)-(1:25), and the acid leaching time is 30min-90min.

[0015] The doping mass ratio of CaO+MgO to high-activity biomass powder is (1:1)-(1:2), and the doping mass ratio of CaO to MgO is (3:1)-(1:3).

[0016] In the impregnation modification step, the solid-liquid mass ratio of the impregnation is controlled to be (1:15)-(1:25), the stirring speed is 600-1200 rpm / min, the temperature is 50-80° C., and the heating time is 2-5 hours.

[0017] In the impregnation modification step, the refrigerator is frozen for 12-24 hours at a temperature of -24°C to (-18°C), and the freeze-drying time is 24-48 hours at a temperature of -90°C to (-60°C).

[0018] In the pyrolysis and carbonization step, the calcination temperature is 300-900° C., the calcination time is 2-3 hours, and the protective gas is argon.

[0019] In the pyrolysis and carbonization step, the heating rate of calcination is controlled at 3-10 °C / min.

[0020] A Ca / Mg-based modified biochar material is prepared by the above preparation method.

[0021] The above-mentioned Ca / Mg-based modified biochar material is used as an adsorbent in adsorbing phosphate in wastewater solution.

[0022] The pH of the wastewater solution is 3-13.

[0023] When the pH value of the wastewater solution is 3-7, the doping mass of MgO is controlled to be greater than that of CaO.

[0024] In view of the problems existing in the background technology, the inventor has made the following improvements:

[0025] 1) A variety of existing biomass materials that can be used as biochar materials have been studied in depth. In view of the treatment of phosphorus-containing wastewater, grapefruit peel is specially selected as the modified raw material. On the one hand, compared with other biomass materials, grapefruit peel has a higher content of cellulose and pectin and a loose structure. When used for the preparation of biochar, it can have a larger specific surface area. Calcium and magnesium sources can be agglomerated on the surface of the biochar material in large quantities, so that it has a large number of active sites, which can more efficiently adsorb phosphorus and is more suitable for treating phosphorus-containing wastewater; on the other hand, the natural components of grapefruit peel contain rich organic acids and antioxidants. These components can promote the pore formation of biochar during pyrolysis, increase the number and types of its surface functional groups, and further enhance its adsorption capacity for pollutants. In addition, grapefruit peel biochar can be made into a slow-release fertilizer after adsorbing phosphorus, which helps to improve the microbial environment of the soil and promote the growth of plant roots, thereby achieving the dual benefits of wastewater treatment and soil improvement. In addition, the renewability of grapefruit peel makes it more economical and sustainable in the production of biochar, meets environmental protection requirements, and helps to reduce the accumulation of agricultural waste and environmental pollution.

[0026] 2) In the pretreatment step, in addition to conventional crushing, screening, washing and drying, an acid leaching activation step is creatively introduced. The acid leaching activation can effectively remove impurities and other inorganic substances on the surface of the grapefruit peel, revealing its internal structure, so that the porosity, specific surface area and activity of the biomass material will be greatly improved, which is conducive to the subsequent pyrolysis process and the formation of biochar. Compared with the prior art, this method is traditionally pretreated only by physical methods, while acid leaching activation uses chemical reactions to more deeply change the surface properties of the material, increase the types and number of functional groups, and thus enhance its adsorption capacity for pollutants. Here, the acid is hydrochloric acid, sulfuric acid or nitric acid with a concentration of 0.1mol / L-1mol / L, and the preferred concentration is 0.5mol / L-0.8mol / L. Within this range, the acid concentration is moderate, which helps to optimize the activation effect; too high a concentration will lead to excessive corrosion of the material, loss of too much organic matter and structure, and reduce the formation of biochar; too low a concentration may not effectively remove impurities, the activation effect is not obvious, and it is difficult to achieve the expected modification effect. The acid leaching time is 30-90 minutes. If the time is too long, it will cause excessive corrosion and damage to the material, affecting the stability of its pore structure; if it is too short, the activation effect of the acid may not be fully exerted, resulting in insufficient treatment of the biomass material, affecting the subsequent biochar preparation and its application effect in the treatment of phosphorus-containing wastewater. By optimizing the type, concentration and immersion time of the acid, the modification effect of grapefruit peel can be maximized, thereby enhancing its application potential as a biochar material.

[0027] 3) In the impregnation step, CaO and MgO are added at the same time, which not only makes the calcium source and magnesium source more stable and the material more consistent, but also introduces the synergistic effect of double metal ions, which has a stronger precipitation effect on phosphorus. The material has good stability and a wide pH application range, and can treat phosphorus-containing wastewater solutions in the pH range of 3-13. Here, the amount of high-activity biomass powder added is controlled to be 1-2 times that of the calcium and magnesium sources. Too much will increase the particle density of the material, affect its pore structure and specific surface area, and reduce its adsorption capacity for pollutants; too little will make the biomass material insufficiently active and unable to fully exert its phosphorus removal effect. The mass ratio of CaO and MgO doping is (3:1)-(1:3). In specific applications, different doping ratios of CaO and MgO can be selected according to the specific pH value of the wastewater. When the pH of the water body is low, the MgO dosage is increased to enhance the removal effect through the precipitation and complexation of magnesium ions and ion exchange. When the pH of the water body is high, the CaO dosage is increased to utilize the precipitation ability of calcium ions to ensure the high stability of the adsorption material in different complex water environments, thereby improving the efficiency of removing phosphorus-containing wastewater.

[0028] 4) In the carbonization step, since the biomass powder prepared from acid-leached grapefruit peel is used as the raw material, during the subsequent pyrolysis carbonization, some impurities and moisture have been removed from the biomass powder, and its carbon content has been increased by acid leaching, thereby overcoming the traditional requirement of strict temperature control. The present invention does not need to strictly control the calcination temperature, and can be freely selected within a wide range of 300-900°C, and the reaction conditions are more relaxed. Furthermore, the calcination heating rate is controlled to be 3-10°C / min to ensure that the pyrolysis process of the material can be fully carried out to form a carbon material with a good pore structure; too fast will cause the surface of the material to overheat and coke, affecting the quality and stability of the final product; too slow may cause the pyrolysis time to be too long, increase energy consumption, and reduce production efficiency. Therefore, a reasonable heating rate and temperature selection are crucial to obtaining high-performance carbonized products.

[0029] In summary, the method of the present invention is simple, the reaction conditions are loose, the raw materials are easily available, and the cost is low. The prepared Ca / Mg-based modified bimetallic modified biochar material has good stability, good pH adaptability, good adsorption effect, and can enhance the adsorption capacity of the carbon material for phosphate. It is particularly suitable for water environments with more complex pollution factors and requires less usage. The Ca / Mg-based modified bimetallic modified biochar material after adsorbing phosphate also has the potential to be used as a phosphate fertilizer. In subsequent studies, it can be applied to farmland and used as a phosphate fertilizer required for crop growth, providing a guarantee for waste utilization in different polluted environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is the SEM image of the carbonized grapefruit peel raw material.

[0031] Figure 2 This is the SEM image of the carbonized CaO-modified grapefruit peel material.

[0032] Figure 3 This is the SEM image of the carbonized MgO-modified grapefruit peel material.

[0033] Figure 4 This is a SEM image of the carbonization of the CaO and MgO composite modified grapefruit peel material in Example 1. DETAILED DESCRIPTION

[0034] Embodiment 1:

[0035] (1) Preparation of Ca / Mg-GCX

[0036] The grapefruit peel was dried and crushed until a 90-mesh fine powder was obtained, and then washed and dried again. 4 g of biomass powder was acid-leached and activated using 1 mol / L hydrochloric acid, with a solid-liquid mass ratio of 1:20 and a soaking time of 60 min. After soaking, it was washed several times until the pH value of the washing liquid was close to neutral, and then it was dried again to obtain a highly active biomass powder. CaO+MgO was mixed with the highly active biomass powder in a doping mass ratio of 1:1, and the CaO and MgO doping mass ratio was 3:1, and distilled water was added, with a solid-liquid mass ratio of 1:20. Stir at 800 rpm for 3 hours at 70 °C. After that, the filter cake was washed with distilled water several times, placed in a -24 °C refrigerator for 12 hours, and then freeze-dried at -90 °C for 48 hours. Finally, the dried intermediate product was placed in a tubular furnace and pyrolyzed and carbonized under an argon protective atmosphere, with a heating rate of 5 °C / min, a calcination temperature of 900 °C, and a calcination time of 2 hours. After calcination, the mixture was cooled naturally and washed with distilled water to remove unreacted components, and finally a Ca / Mg-based modified biochar material Ca / Mg-GCX-900 (representing the material obtained under 900°C) was obtained.

[0037] (2) Application

[0038] 0.1 g of Ca / Mg-GCX-900 material was weighed and added into 100 ml of phosphorus-containing (100 mg / L) solution at pH = 13. The reaction was allowed to proceed for 24 h, followed by solid-liquid separation. The adsorption efficiency was calculated to be 96.28%.

[0039] (3) The SEM image of the Ca / Mg-based modified biochar material Ca / Mg-GCX-900 prepared in Example 1 is shown in Figure 4 In order to illustrate the difference in microstructure under electron microscope, the SEM image of carbonized grapefruit peel raw material is provided (see Figure 1 The preparation method thereof is the same as that of Example 1 except that the addition of CaO+MgO is omitted) and the SEM image of the carbonization of CaO-modified grapefruit peel material (see Figure 2The preparation method thereof is the same as that of Example 1 except that the addition of MgO is omitted), and the SEM image of the carbonization of MgO-modified grapefruit peel material (see Figure 3 The preparation method is the same as in Example 1 except that the addition of CaO is omitted. By comparing the four figures, it can be seen that there are obvious differences in the microstructures of the four figures. Specifically, Figure 1 The surface of the grapefruit peel raw material has a rich interlayer structure after carbonization, with a large specific surface area but relatively flat and fewer pores. Figure 2 It shows that after CaO modification, many large particles appeared on the surface of the material. It should be that the calcium source was introduced and the active sites on the surface of the material became more, indicating that the addition of CaO promoted the surface activation of biochar. Figure 3 The MgO-modified biochar in the sample showed more complex microscopic changes. The increase in the number and size of pores further increased its specific surface area, and there were a lot of small particles on the surface. It should be that the magnesium source was introduced and the active sites were further increased, which was conducive to the improvement of adsorption performance.

[0040] at last, Figure 4 The Ca / Mg-GCX-900 material combines the advantages of Ca and Mg, showing richer microstructural characteristics, more diverse pore distribution, and more particles on the surface after the introduction of calcium and magnesium composites. The active sites are richer than those of single metal modification, which may provide a better performance basis for its application in environmental remediation and resource recycling. This shows that the modification process effectively enhances the physical properties and potential application value of biochar.

[0041] Embodiment 2:

[0042] (1) Preparation of Ca / Mg-GCX

[0043] The grapefruit peel was dried and crushed until a fine powder of 80 mesh was obtained, and then washed and dried again. 4g of biomass powder was acid-leached and activated using 0.5mol / L hydrochloric acid, with a solid-liquid mass ratio of 1:20 and a soaking time of 40min. After soaking, it was washed several times until the pH value of the washing liquid was close to neutral, and then it was dried again to obtain a highly active biomass powder. CaO+MgO was mixed with the highly active biomass powder at a doping mass ratio of 1:1.5, and the CaO and MgO doping mass ratio was 1:1, and distilled water was added, with a solid-liquid mass ratio of 1:20. Stir at 70°C at a speed of 800rpm for 3 hours. After that, the filter cake was washed with distilled water several times, placed in a -24°C refrigerator for 12 hours, and then freeze-dried at -90°C for 48 hours. Finally, the dried intermediate product was placed in a tubular furnace and pyrolyzed and carbonized under an argon protective atmosphere, with a heating rate of 5°C / min, a calcination temperature of 500°C, and a calcination time of 2 hours. After calcination, the mixture was cooled naturally and washed with distilled water to remove unreacted components, and finally a Ca / Mg-based modified biochar material Ca / Mg-GCX-500 (representing the material obtained under 500°C) was obtained.

[0044] (2) Application

[0045] 0.1 g of Ca / Mg-GCX-500 material was weighed and added into 100 ml of phosphorus-containing (100 mg / L) solution at pH = 7. The reaction was allowed to proceed for 24 h, followed by solid-liquid separation. The adsorption efficiency was calculated to be 98.06%.

[0046] Embodiment 3:

[0047] (1) Preparation of Ca / Mg-GCX

[0048] The grapefruit peel was dried and crushed until a 60-mesh fine powder was obtained, and then washed and dried again. 4 g of biomass powder was acid-leached and activated using 0.1 mol / L hydrochloric acid, with a solid-liquid mass ratio of 1:20 and a soaking time of 30 min. After soaking, it was washed several times until the pH value of the washing liquid was close to neutral, and then it was dried again to obtain a highly active biomass powder. CaO+MgO was mixed with the highly active biomass powder in a doping mass ratio of 1:2, and the CaO and MgO doping mass ratio was 1:3, and distilled water was added, with a solid-liquid mass ratio of 1:20. Stir at 800 rpm at 70 °C for 3 hours. After that, the filter cake was washed with distilled water several times, placed in a -24 °C refrigerator for 12 hours, and then freeze-dried at -90 °C for 48 hours. Finally, the dried intermediate product was placed in a tubular furnace and pyrolyzed and carbonized under an argon protective atmosphere, with a heating rate of 5 °C / min, a calcination temperature of 300 °C, and a calcination time of 2 hours. After calcination, the mixture was cooled naturally and washed with distilled water to remove unreacted components, and finally a Ca / Mg-based modified biochar material Ca / Mg-GCX-300 (representing the material obtained under 300°C) was obtained.

[0049] (2) Application

[0050] 0.1 g of Ca / Mg-GCX-300 material was weighed and added into 100 ml of phosphorus-containing (100 mg / L) solution at pH = 3. The reaction was allowed to proceed for 24 h, followed by solid-liquid separation. The adsorption efficiency was calculated to be 91.59%.

[0051] Comparative Example 1:

[0052] (1) Preparation of Ca / Mg-GCX

[0053] The banana peel was dried and crushed until a 90-mesh fine powder was obtained, and then washed and dried again. 4 g of biomass powder was acid-leached and activated using 1 mol / L hydrochloric acid, with a solid-liquid mass ratio of 1:20 and a soaking time of 60 min. After soaking, it was washed several times until the pH value of the washing liquid was close to neutral, and then it was dried again to obtain a highly active biomass powder. CaO+MgO was mixed with the highly active biomass powder in a doping mass ratio of 1:1, and the CaO and MgO doping mass ratio was 3:1, and distilled water was added, with a solid-liquid mass ratio of 1:20. Stir at 70 °C at a speed of 800 rpm for 3 hours. After that, the filter cake was washed with distilled water several times, placed in a -24 °C refrigerator for 12 hours, and then freeze-dried at -90 °C for 48 hours. Finally, the dried intermediate product was placed in a tubular furnace and pyrolyzed and carbonized under an argon protective atmosphere, with a heating rate of 5 °C / min, a calcination temperature of 900 °C, and a calcination time of 2 hours. After calcination, the mixture was cooled naturally and washed with distilled water to remove unreacted components, and finally a Ca / Mg-based modified biochar material Ca / Mg-GCX-900 (representing the material obtained under 900°C) was obtained.

[0054] (2) Application

[0055] 0.1 g of Ca / Mg-GCX-900 material was weighed and added into 100 ml of phosphorus-containing (100 mg / L) solution at pH = 13. The reaction was allowed to proceed for 24 h, followed by solid-liquid separation. The adsorption efficiency was calculated to be 80.28%.

[0056] Summary: From the comparison between Comparative Example 1 and Example 1, it can be seen that changing the original biomass material for the experiment will cause a large deviation in the adsorption efficiency. This further verifies the superiority of grapefruit peel as a base material.

[0057] Comparative Example 2:

[0058] (1) Preparation of Ca / Mg-GCX

[0059] The grapefruit peel was dried and crushed until a 90-mesh fine powder was obtained, and then washed and dried again. CaO+MgO was mixed with high-activity biomass powder in a doping mass ratio of 1:1, and the doping mass ratio of CaO and MgO was 3:1, and distilled water was added, and the solid-liquid mass ratio was 1:20. Stir at 70°C at a speed of 800rpm for 3 hours. After that, the filter cake was washed with distilled water several times, placed in a -24°C refrigerator for 12 hours, and then freeze-dried at -90°C for 48 hours. Finally, the dried intermediate product was placed in a tubular furnace and pyrolyzed and carbonized under an argon protective atmosphere, with a heating rate of 5°C / min, a calcination temperature of 900°C, and a calcination time of 2 hours. After the calcination, it was naturally cooled and washed with distilled water to remove the unreacted components, and the Ca / Mg-GCX-900 (representing the material obtained under 900°C) was finally obtained.

[0060] (2) Application

[0061] 0.1 g of Ca / Mg-GCX-900 material was weighed and added into 100 ml of phosphorus-containing (100 mg / L) solution at pH = 13. The reaction was allowed to proceed for 24 h, followed by solid-liquid separation. The adsorption efficiency was calculated to be 78.65%.

[0062] Summary: From the comparison between Comparative Example 2 and Example 1, it can be seen that the final adsorption efficiency of the original biomass material without acid leaching pre-treatment is far less than that of the material after acid leaching treatment, which further verifies the superiority of acid leaching pre-treatment.

[0063] Calculation results:

[0064] Phosphate adsorption efficiency:

[0065] η=(C0-C t ) / C0×100%

[0066] Where η is the adsorption rate, C0 is the initial concentration, C t is the concentration after a fixed reaction time.

Claims

1. A method for preparing a Ca / Mg-based modified bimetallic modified biochar material, characterized in that: The following steps are involved: Pretreatment: After the biomass material is dried, it is crushed, sieved, washed and dried, and then acid-leached for activation, and then washed and dried again to obtain a highly active biomass powder, wherein the biomass material is grapefruit peel; Impregnation modification: the highly active biomass powder obtained in the pretreatment step is fully mixed with CaO and MgO, distilled water is added, and the mixture is impregnated under heating and stirring conditions, and then solid-liquid separation is performed. After the filter cake is washed multiple times, it is freeze-dried and sieved to obtain a preliminary modified intermediate product; Pyrolysis carbonization: The intermediate product obtained in the impregnation modification step is calcined under a protective atmosphere, and the product is naturally cooled, washed, and dried to obtain a Ca / Mg-based modified bimetallic modified biochar material.

2. The method for preparing the Ca / Mg-based modified biochar material according to claim 1, characterized in that: In the pretreatment step, the biomass powder is sieved with a mesh size of 60-90 meshes.

3. The method for preparing the Ca / Mg-based modified biochar material according to claim 1 or 2, characterized in that: In the pretreatment step, the acid used for acid leaching activation is hydrochloric acid, nitric acid or sulfuric acid with a concentration of 0.1 mol / L-1 mol / L, the solid-liquid mass ratio of the immersion is controlled to be (1:10)-(1:25), and the acid leaching time is 30min-90min.

4. The method for preparing the Ca / Mg-based modified biochar material according to claim 1, characterized in that: In the impregnation modification step, the doping mass ratio of CaO+MgO to high-activity biomass powder is (1:1)-(1:2), and the doping mass ratio of CaO and MgO is (3:1)-(1:3).

5. The method for preparing the Ca / Mg-based modified biochar material according to claim 1 or 4, characterized in that: In the impregnation modification step, the solid-liquid mass ratio of the impregnation is controlled to be (1:15)-(1:25), the stirring speed is 600-1200 rpm / min, the temperature is 50-80° C., and the heating time is 2-5 hours.

6. The method for preparing the Ca / Mg-based modified biochar material according to claim 5, characterized in that: In the impregnation modification step, the refrigerator is frozen for 12-24 hours at a temperature of -24°C to (-18°C), and the freeze-drying time is 24-48 hours at a temperature of -90°C to (-60°C).

7. The method for preparing the Ca / Mg-based modified biochar material according to claim 1, characterized in that: In the pyrolysis and carbonization step, the calcination temperature is 300-900° C., the calcination time is 2-3 hours, and the protective gas is argon.

8. The method for preparing the Ca / Mg-based modified biochar material according to claim 1 or 7, characterized in that: In the pyrolysis and carbonization step, the heating rate of calcination is controlled at 3-10 °C / min.

9. A Ca / Mg-based modified biochar material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 8.

10. An application of a Ca / Mg-based modified biochar material, characterized in that: The Ca / Mg-based modified biochar material described in claim 9 is used as an adsorbent to adsorb phosphate in wastewater solutions.

11. The use of the Ca / Mg-based modified biochar material according to claim 10, characterized in that: The pH of the wastewater solution is 3-13.

12. The use of the Ca / Mg-based modified biochar material according to claim 10, characterized in that: When the pH value of the wastewater solution is 3-7, the doping mass of MgO is controlled to be greater than that of CaO.

Citation Information

Patent Citations

  • Preparation method and application of Mg / Ca loaded modified tobacco stalk biochar

    CN112191229A

  • Iron and magnesium modified biochar as well as preparation method and application thereof

    CN113522241A

  • Magnetic activated carbon adsorption material and preparation method

    CN109289775A

  • Preparation method of modified sludge biochar and obtained biochar and application

    CN114029035A

  • Shaddock peel modified adsorbing material as well as preparation method and application thereof

    CN116371370A

Cited By

  • Application of eggshell-doped shaddock peel biochar in promoting degradation of sulfonylurea herbicide residues

    CN120268786A

  • Aquatic plant planting matrix filler for sewage treatment and preparation method thereof

    CN120398273A

  • Biochar fertilizing method and biochar fertilizer and application thereof

    CN120483811A

  • Method for recovering nitrogen and phosphorus in biogas slurry based on high-purity cellulose carbon

    CN121698427A